The Interplay of Perceived Usefulness, Security, and Lifestyle in Shaping Gen Z's QRIS Usage Intention: A Path Towards a Cashless Padang - Rayhan Anugerah Hadikusuma; Thamrin, Thamrin (Universitas Negeri Padang, 2024)
This study aims to examine the effects of Perceived Benefits and Perceived Security on the Continuance Usage Intention of QRIS among Gen Z in the context of a Cashless Society, with Lifestyle as a Moderating Variable. The research employs an associative methodology to identify relationships between multiple independent variables and the dependent variable. The study population comprises Gen Z individuals in Padang City, with a sample of 150 QRIS users selected through purposive sampling within a non-probability sampling framework. Data were collected via questionnaires using a Likert Scale and analyzed using SmartPLS software. The findings reveal that: (1) Perceived Benefits have a positive and significant effect on Continuance Usage Intention; (2) Perceived Security has a positive but non-significant effect on Continuance Usage Intention; (3) Lifestyle does not moderate the effect of Perceived Benefits on Continuance Usage Intention; and (4) Lifestyle weakens the relationship between Perceived Security and Continuance Usage Intention.